353 Preterm Birth and the Metabolic Syndrome: a Systematic Review and Meta-Analysis. (October 2012) - Parkinson, JR; Hyde, MJ; Gale, C; Santhakumaran, S; Modi, N
Abstract : Background and Aims: Preterm birth is associated with raised blood pressure (BP) and other features of the metabolic syndrome in later life, but effect sizes and biological mechanisms are unknown. We conducted a meta-analysis to address these associations in adult life. Methods: We performed a systematic review and meta-analysis of studies in which metabolic syndrome associated indices were compared in adults (≥18 years of age) born preterm (< 37 weeks gestation) and at term (37–42 weeks gestation). Outcome measures included; systolic blood pressure (SBP), diastolic blood pressure (DBP), BMI, percentage fat mass and fasting plasma levels of lipids, glucose and insulin. Results: Data from 27 studies and 306, 123 adults (16, 094 preterm, 290, 029 term) were included, with an average outcome age of 26.1 years. In adults, preterm compared with full-term birth was associated with significantly higher SBP (mean difference [95% confidence interval]: 4.2mmHg [2.7, 5.7], p<0.001), DBP (2.7mmHg [1.2, 4.2], p<0.001) and low density lipoprotein (LDL) (0.14mmol/L [0.05, 0.22], p=0.01). Meta-regression revealed a significant gender effect, with 3.0mmHg greater SBP in preterm compared to term women than in preterm-term men (95%CI: 1.3, 4.7, p=0.002); for DBP this difference was 2.1mmHg greater (0.6, 3.6, p=0.009). Conclusions: Preterm compared to term birth, is associated with higher blood pressure and LDL in adult life. Women born preterm appear to be at greater risk than men born preterm. Follow-up of older subjects born preterm will be required to determine if the effects we observe are exacerbated by age.